A Note on the Structure of Hebrews 10:11–13 - Akagi, Kai (Novum Testamentum, 2023)
Lexical, syntactical, and semantic correspondence demonstrates that Heb 10:11–13 consists of a concentric structure not discussed in the commentary literature. Obser‑ vation of this structure clarifies the number of contrasts that appear in the sentence spanning these verses and provides additional data informing the debated question of whether the phrase εἰς τὸ διηνεκές in Heb 10:12 modifies the preceding participle προσενέγκας or the following verb ἐκάθισεν. This structure furthermore serves as one more example of the emphasis on the singularity of Jesus’s sacrifice in Hebrews.